ANALISIS YURIDIS PELANGGARAN HAK CIPTA PADA PERBUATAN MEMFOTOKOPI BUKU ILMU PENGETAHUAN - Sastrawan, Gede; Sastrawan, Gede (Program Studi Ilmu Hukum, Jurusan Hukum dan Kewarganegaraan, Fakultas Hukum dan Ilmu Sosial, Universitas Pendidikan Ganesha, 2021)
This article discusses the Juridical Analysis of Copyright Infirigement On The Act Of Photocopying Books of Science. Copyright is a part of Intellectual Property Rights (HKI). The copyright phrase comes from a foreign term, namely Copyrights. The term Copyrights was first put forward in the Berne Comvertion (International Convention on Copyright concerning the protection of Art and Literature) which was held in 1886. According to Article 1 number (1) of Law Number 28 of 2014 concerning Copyright, it states that